New cetacean Delta R values for Arctic North America and their implications for marine-mammal-based palaeoenvironmental reconstructions - Furze, Mark F.A.; Pieńkowski, Anna J.; Coulthard, Roy D. (My University, 2014)
Radiocarbon-dated marine mammal remains from emergent Arctic coastlines have frequently been used to reconstruct Holocene sea-ice histories. The use of such reconstructions has hitherto been complicated by uncertain marine reservoir corrections precluding meaningful intercomparisons with data reported in calibrated or sidereal years. Based on an exhaustive compilation of previously published marine mammal radiocarbon dates (both live-harvested materials and subfossils) from the Canadian Arctic Archipelago (CAA), new, statistically-derived delta (super 13) C and Delta R values are provided. Average delta (super 13) C values are: -16.1 + or - 1.1 ppm (bone collagen; n = 193) for bowhead (Balaena mysticetus); -14.4 + or - 0.5 ppm (n = 44; dentine) for beluga (Delphinapterus leucas); -14.8 + or - 1.9 ppm (teeth and tusks; n = 18) and -18.0 + or - 4.7 ppm (n = 9; bone collagen) for walrus (Odobenus rosmarus). Delta R values are 170 + or - 95 (super 14) C years for bowhead (n = 23) and 240 + or - 60 (super 14) C years for beluga (n = 12). Scarce data preclude calculation of meaningful, statistically robust walrus Delta R. Using the new Delta R values, an expanded and revised database of calibrated bowhead dates (651 dates; many used in previous CAA sea-ice reconstructions) shows pronounced late Quaternary spatio-temporal fluctuations in bone abundance. Though broadly resembling earlier bowhead subfossil frequency data, analysis of the new expanded database suggests early- and mid-Holocene increases in whale abundance to be of longer duration and lower amplitude than previously considered. A more even and persistent spread of infrequent low-abundance remains during "whale free" intervals is also seen. The dominance of three eastern regions (Prince Regent Inlet & Gulf of Boothia; Admiralty Inlet; Berlinguet Inlet/Bernier Bay) in the CAA data, collectively contributing up to 88% of all subfossil remains in the mid-Holocene, is notable. An analysis of calibrated regional sea-level index points suggests that severance of the Admiralty Inlet-Gulf of Boothia marine channel due to isostatically-driven regression may have played a significant role in enhanced whale mortality during this interval. Comparisons between the newly calibrated bowhead data and other regional sea-ice proxy data further highlight spatial and temporal discrepancies, potentially due to regional asynchronicities and variable sensitivities in proxy response to climate and oceanographic forcing. However, the limited number of deglacial-postglacial marine records continues to hamper extensive intercomparisons between marine mammal and other proxy datasets. Nevertheless, an examination of assumptions inherent in linking bowhead subfossil frequencies, population densities, and sea-ice thickness and distribution, shows that such relationships are highly complex. Factors such as broad sea-ice preferences, variable mortality rates and causes, long distance carcass transport, variable coastline and basin/channel geometries, and changing emergence rates all complicate the correlation of whale bone abundance to sea-ice histories.
Keywords: radiocarbon calibration; reservoir correction; bowhead whale; Canadian Arctic